Domestic violence: knowledge, attitudes, and clinical practice of selected UK primary healthcare clinicians - Ramsay, Jean (Royal College of General Practitioners, 2012)
BACKGROUND: Domestic violence affects one in four women and has significant health consequences. Women experiencing abuse identify doctors and other health professionals as potential sources of support. Primary care clinicians agree that domestic violence is a healthcare issue but have been reluctant to ask women if they are experiencing abuse. AIM: To measure selected UK primary care clinicians’ current levels of knowledge, attitudes, and clinical skills in this area. DESIGN AND SETTING: Prospective observational cohort in 48 general practices from Hackney in London and Bristol, UK. METHOD: Administration of the Physician Readiness to Manage Intimate Partner Violence Survey (PREMIS), comprising five sections: responder profile, background (perceived preparation and knowledge), actual knowledge, opinions, and practice issues. RESULTS: Two hundred and seventy-two (59%) clinicians responded. Minimal previous domestic violence training was reported by participants. Clinicians only had basic knowledge about domestic violence but expressed a positive attitude towards engaging with women experiencing abuse. Many clinicians felt poorly prepared to ask relevant questions about domestic violence or to make appropriate referrals if abuse was disclosed. Forty per cent of participants never or seldom asked about abuse when a woman presented with injuries. Eighty per cent said that they did not have an adequate knowledge of local domestic violence resources. GPs were better prepared and more knowledgeable than practice nurses; they also identified a higher number of domestic violence cases. CONCLUSION: Primary care clinicians’ attitudes towards women experiencing domestic violence are generally positive but they only have basic knowledge of the area. Both GPs and practice nurses need more comprehensive training on assessment and intervention, including the availability of local domestic violence services.